Transition et socialisation professionnelles d’une nouvelle professeure d’université : dynamiques collectives et institutionnelles en question - Claire Duchesne; Lucie Le Callonnec; Nathalie Gagnon (Recherches en Éducation)
In the North-American context, most new university professors come to better understand what a faculty position entails while they are completing their doctoral studies, and if they have had the opportunity to work as a research assistant or a lecturer, they have a fairly accurate idea of what awaits them. PhD students are usually aware that the workload of a professor can be heavy. Once employed, they realize that this fear may have been well-founded, and that the workload may even exceed their initial apprehensions. Based on the analysis of one semi-structured interview, this article examines the process of transition as well as the steps and challenges of the process of socialisation of a new university professor beginning her faculty career. The importance and need for more directed institutional support and for a welcoming team for early career professors will also be discussed in this article.